Phylogenetic analysis of the true water bugs (Insecta: Hemiptera: Heteroptera: Nepomorpha): evidence from mitochondrial genomes - Hua, Jimeng (BioMed Central, 2009)
BACKGROUND: The true water bugs are grouped in infraorder Nepomorpha (Insecta: Hemiptera: Heteroptera) and are of great economic importance. The phylogenetic relationships within Nepomorpha and the taxonomic hierarchies of Pleoidea and Aphelocheiroidea are uncertain. Most of the previous studies were based on morphological characters without algorithmic assessment. In the latest study, the molecular markers employed in phylogenetic analyses were partial sequences of 16S rDNA and 18S rDNA with a total length about 1 kb. Up to now, no mitochondrial genome of the true water bugs has been sequenced, which is one of the largest data sets that could be compared across animal taxa. In this study we analyzed the unresolved problems in Nepomorpha using evidence from mitochondrial genomes. RESULTS: Nine mitochondrial genomes of Nepomorpha and five of other hemipterans were sequenced. These mitochondrial genomes contain the commonly found 37 genes without gene rearrangements. Based on the nucleotide sequences of mt-genomes, Pleoidea is not a member of the Nepomorpha and Aphelocheiroidea should be grouped back into Naucoroidea. Phylogenetic relationships among the superfamilies of Nepomorpha were resolved robustly. CONCLUSION: The mt-genome is an effective data source for resolving intraordinal phylogenetic problems at the superfamily level within Heteroptera. The mitochondrial genomes of the true water bugs are typical insect mt-genomes. Based on the nucleotide sequences of the mt-genomes, we propose the Pleoidea to be a separate heteropteran infraorder. The infraorder Nepomorpha consists of five superfamilies with the relationships (Corixoidea + ((Naucoroidea + Notonectoidea) + (Ochteroidea + Nepoidea))).